KECENDERUNGAN PEMILIHAN DAN DUPLIKASI TEMA SKRIPSI SERTA DAMPAKNYA PADA PENGEMBANGAN ILMU PERPUSTAKAAN DAN INFORMASI - Masruri, Anis (Fakultas Adab dan Ilmu Budaya UIN Sunan Kalijaga Yogyakarta, 2018)
The purpose of this paper is to know the trend of the selection and duplication of undergraduate theses themes and their influence on the development of library and information science. This research is conducted at the Department of Library Science of Faculty of Adab and Cultural Sciences at UIN Sunan Kalijaga Yogyakarta. Based on the research on 236 undergraduate theses, there are 10 main themes i.e., User Study, Library Management, Library Utilization, Reading Interest, Computer Technology, Bibliometrics Statistics, Search and Storage Information, Psychology, Archive, and Scientific Communication. Further, this research finds that the development of library science and information has not led to deep scientific integration and interconnection.